2002
DOI: 10.1093/bja/aef287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intramuscular administration of lidocaine or bupivacaine on induction and maintenance doses of propofol evaluated by bispectral index

Abstract: I.M. administered local anaesthetics are associated with a decrease in both the induction and maintenance doses of propofol during total i.v. anaesthesia and a reduction in haemodynamic responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 12 publications
(7 reference statements)
0
40
0
Order By: Relevance
“…lidocaine infusion has a minimal alveolar concentration (MAC)-sparing effect of 10%~28%. In a later study (Senturk et al, 2002), an i.v. anesthetic was used instead of inhalational anesthetics, and lidocaine was administered via the i.m.…”
Section: Discussionmentioning
confidence: 94%
“…lidocaine infusion has a minimal alveolar concentration (MAC)-sparing effect of 10%~28%. In a later study (Senturk et al, 2002), an i.v. anesthetic was used instead of inhalational anesthetics, and lidocaine was administered via the i.m.…”
Section: Discussionmentioning
confidence: 94%
“…However, in ponies the reduction can reach up to 70% of halothane on MAC (DOHERTy; FRAZIER, 1998). Senturky et al (2002) observed that a single dose of lidocaine by intramuscular injection in humans was sufficient to reduce the necessary dose of propofol to maintain anesthesia by 29%. Mannarino (2002) found that applying 2.5 mg/kg followed by the infusion of 250 μg/kg/minute resulted in a reduction of 21% in the required propofol dose in dogs.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore suggest that inhibitory actions of local anesthetics on I h in thalamocortical cells and cortical or hippocampal pyramidal neurons may contribute to their central anesthetic-sparing actions. In addition, because inhibition of HCN channels in sensory neurons can reduce pain sensation (Chaplan et al, 2003), it is possible that anesthetic sparing (DiFazio et al, 1976;Himes et al, 1977;Senturk et al, 2002) or analgesic actions in postoperative or neuropathic contexts (Kingery, 1997;Smith et al, 2004) could be due to effects of systemic local anesthetics on HCN1 or HCN2 subunits expressed in nociceptors (Chaplan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine is the most important class 1B antiarrhythmic drug; it is used intravenously for the treatment of ventricular arrhythmias (Trujillo and Nolan, 2000;Pinter and Dorian, 2001). Lidocaine reduces minimal alveolar concentration of volatile anesthetics for the suppression of responses to painful stimuli in animals by 20 to 40% (DiFazio et al, 1976;Himes et al, 1977;Smith et al, 2004) and decreases the requirement of intravenous anesthetic propofol (Senturk et al, 2002). The local anesthetic lidocaine can produce ϳ0.4 minimal alveolar concentration (low-dose systemic application) (DiFazio et al, 1976) and decrease the bispectral index to 0 (higher-dose systemic application) (Gaughen and Durieux, 2006).…”
Section: Introductionmentioning
confidence: 99%